What Is at Stake in the Formalization of a Chronostratigraphic Unit? A Case Study on the Anthropocene. Issue 5 (25th December 2022) - Bobadilla, Hernán
Abstract: The prospective formalization of the Anthropocene as a chronostratigraphic unit by the International Commission on Stratigraphy has been intensely debated. This paper explores and assesses the stakes of this process from a philosophical perspective. I distinguish two senses of formalization—the descriptive and the evaluative—and argue that: 1) there are descriptive and evaluative formalizations of the Anthropocene beyond the confines of the ICS; 2) incoherencies between Anthropocene proposals and the ICS's current tenets are not a decisive reason for deferring descriptive formalization; and 3) the prospective evaluative formalization of the Anthropocene by the ICS would be impactful.